The Role Of Digital Health Interventions in Managing Lifestyle Diseases - Amine El Mekkaoui; Rachida Bensaid (International Journal of Health and Medicine, 2024)
This study explores how digital health interventions, such as mobile health apps and wearable devices, contribute to the management of lifestyle diseases like diabetes and hypertension. By examining user data from various digital platforms, the research highlights improvements in patient adherence, monitoring capabilities, and self-management skills. The findings suggest that digital health interventions can empower patients to manage their conditions more effectively and reduce the burden on healthcare systems.